2016
DOI: 10.11604/pamj.2016.24.332.9462
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of sexual assault in Usmanu Danfodiyo University Teaching Hospital, Sokoto, Nigeria

Abstract: IntroductionSexual violence is an important public health problem of growing concern all over the world. This study was conducted to determine the prevalence and pattern of sexual assault managed in Usmanu Danfodiyo University Teaching Hospital Sokoto, Nigeria.MethodsIt was a retrospective study that looked into cases of sexual assault admitted into the hospital between January 2010 and December 2014. Information on patients’ biodata, and relevant details on the cases were extracted from the patients’ case fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 21 publications
4
22
1
Order By: Relevance
“…Our finding that majority of the survivors were female is in keeping with previous studies which have reported that majority of sexual assault survivors are female. 15 , 24 , 25 Studies carried out in India, 18 Bangladesh 26 and Uganda 27 have also reported low rates of sexual assault in male gender as shown in this study. It is, however, important that as preventive measures are directed towards females, male survivors and males at risk are not neglected.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Our finding that majority of the survivors were female is in keeping with previous studies which have reported that majority of sexual assault survivors are female. 15 , 24 , 25 Studies carried out in India, 18 Bangladesh 26 and Uganda 27 have also reported low rates of sexual assault in male gender as shown in this study. It is, however, important that as preventive measures are directed towards females, male survivors and males at risk are not neglected.…”
Section: Discussionsupporting
confidence: 68%
“…This finding is similar to that reported in Sokoto State, Nigeria, that 91.2% of survivors were assaulted by only one perpetrator. 24 Similarly, reports from medico legal clinics in Johannesburg, South Africa, following rape found that majority involved one perpetrator. 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anambra State had a reported a prevalence of 0.42 (Ikechebelu et al, 2008). Interestingly, other researchers from Abakaliki in Ebonyi State (South-east, Nigeria) and Zaria in Kaduna State (North-west, Nigeria); were noted to have recorded similar prevalence rates of 0.9%and 0.84%respectively (Chinawa et al, 2013;Mairo, 2016). Similarly, studies conducted in Lagos State and Ile-ifein Osun State both in (South-west, Nigeria) reported prevalence of 0.76% and 0.69% (Badejok, 2014) respectively.…”
Section: Discussionmentioning
confidence: 83%
“…However, this could also be attributed to the fact that male sexual assault survivors are less likely to report the incident (Chinawa et al, 2013;Stewart & Frussel, 2000;Ashimi, Amole, & Ugwa, 2015). In a research conducted in Suleja, Nigeria, (Mairo et al, 2016) they documented two males (7%) among 29 survivors of child-sexual assault, thus demonstrating the existence of male sexual assault in the country. One reason being adduced as probably being responsible for high vulnerability of children to sexual assault is the evolving trend in our homes due to the need for both parents to be engaged in one form of business or another as a result of ailing economy thereby breeding under parenting with attendant depressed supervision of children.…”
Section: Discussionmentioning
confidence: 99%